Cellulase interacts with Lactobacillus plantarum to affect chemical composition, bacterial communities, and aerobic stability in mixed silage of high-moisture amaranth and rice straw. (November 2020) - Mu, Lin; Xie, Zhan; Hu, Longxing; Chen, Guihua; Zhang, Zhifei
Highlights: Ensiling amaranth with rice straw is a good method for amaranth preservation. L. plantarum and cellulase improved silage quality. Combination of L. plantarum and cellulase decreased Enterobacteriaceae abundance. Silage treated with L. plantarum and cellulase showed best silage quality. Abstract: The objective was to evaluate effects of Lactobacillus plantarum and/or cellulase on fermentation, aerobic stability and bacterial community of mixed high-moisture amaranth (AF) and rice straw (RS) silage. The mixtures were treated with no addition (C), L. plantarum (L), cellulase (F) and their combination (LF). Additives increased the abundances of Lactobacillus and reduced the abundances of Weissella, Pediococcus, Lactococcus, decreased pH, acetic acid, ammonia nitrogen and increased lactic acid concentration as compared to C silage over the ensiling period. The LF silage had the highest lactic acid concentration among all silages over the 7 d of ensiling and also the lowest abundance of Enterobacteriaceae over 30 d of ensiling. Aerobic spoilage occurred in C and LF silages after 2 d of aerobic exposure, whereas the L and F silages remained stable > 4 d. In conclusion, silage treated with LF showed best silage quality.